Keandalan Debit Intake Kalibawang Sungai Progo - Marhendi, Teguh (Department of Civil Engineering, Diponegoro University, 2006)
Requirement will irrigate by crop do not forever can be fulfilled by rainwater naturally. At dry season amount of water required taken away from by absolute crop of river debit or source of other water. On the contrary at area owning rainfall enough and flatten during the year, supply irrigate the irrigation is only just needed again. Target of this research is to analyse the reliability charge the river Progo to importance of planning of giftÂ irrigate the irrigation of at Area of Irrigation Kalibawang and Enamoured each;every season plant and also, analysing balance irrigate at Area of Irrigation Kalibawang and Enamoured. Result of Research indicate that the availibility of water in intake kalibawang still answer the demand of to fulfill amount of water required in area of irrigation Kalibawang and Enamoured. This Matter is visible from result analyse the water balance indicating that pledge debit 80 % still can fulfill amount of water required in both the irrigation area Thereby the availibility of water in intake kalibawang give the security to plan of amount of water required to all farmer in both irrigation area.Keywords: requirement, reliability, availibility, irrigationPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3934[How to cite: Marhendi, T., 2006, Keandalan Debit Intake Kalibawang Sungai Progo, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 56-62]